The role of organizational virtuousness in achieving organizational prosperity An exploratory study of the opinions of a sample Academic Staff at the University of Zakho - Mustafa, Khawla; Amin, Hinar (Humanities Journal of University of Zakho, 2023)
This study aims to know the role of organizational virtuousness in achieving organizational prosperity at the University of Zakho, and the study was adopted on the descriptive-analytical approach, and a set of main and secondary hypotheses were adopted that tested in the (7) faculties of Zakho University, A number of questions were set and answered by (156) faculty members and for the purposes of data collection, the questionnaire was designed as a main tool in collecting data related to the field aspects. The data was analyzed by adopting a set of statistical methods using the (SPSS.v.26) program, to analyze the correlation and impact of the aspects of the study variables. The study reached a set of conclusions, the most important of which is the existence of a moral correlation and impact between organizational virtuousness and organizational prosperity. which it possesses and its competencies to face competition and the conditions of the surrounding environment, as well as the need for the researched colleges to adopt the variables of the current study and its dimensions to achieve organizational prosperity and according to the model adopted by the study